2018
DOI: 10.1038/s41593-018-0156-7
|View full text |Cite
|
Sign up to set email alerts
|

mTORC2, but not mTORC1, is required for hippocampal mGluR-LTD and associated behaviors

Abstract: The mechanistic target of rapamycin complex 1 (mTORC1) has been reported to be necessary for metabotropic glutamate receptor-mediated long-term depression (mGluR-LTD). Here we found that mTORC1-deficient mice exhibit normal hippocampal mGluR-LTD and associated behaviors. Moreover, rapamycin blocks mGluR-LTD in mTORC1-deficient mice. However, both rapamycin and mGluR activation regulate mTOR complex 2 (mTORC2) activity, and mTORC2-deficient mice show impaired mGluR-LTD and associated behaviors. Thus, mTORC2 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…Whereas mTOR complex 1 (mTORC1) is a master regulator of cap-dependent translation (Darnell and Klann, 2013), mTORC2 is a central regulator of the actin cytoskeleton through its actions on the actin-depolymerizing factor cofilin (Costa-Mattioli and Monteggia, 2013; Laplante and Sabatini, 2012; see also below). Moreover, mTORC2 (but not mTORC1) has been shown to be critical to mGluR-LTD and related behaviors (Zhu et al, 2018).…”
Section: Molecular Signalingmentioning
confidence: 99%
“…Whereas mTOR complex 1 (mTORC1) is a master regulator of cap-dependent translation (Darnell and Klann, 2013), mTORC2 is a central regulator of the actin cytoskeleton through its actions on the actin-depolymerizing factor cofilin (Costa-Mattioli and Monteggia, 2013; Laplante and Sabatini, 2012; see also below). Moreover, mTORC2 (but not mTORC1) has been shown to be critical to mGluR-LTD and related behaviors (Zhu et al, 2018).…”
Section: Molecular Signalingmentioning
confidence: 99%
“…It is well known that rapamycin blocks hippocampal mGluR-LTD (Hou and Klann, 2004), initially suggesting that protein synthesis mediated by mTORC1 is necessary for this plasticity. Nevertheless, chronic treatment or high concentrations of rapamycin also inhibit mTORC2 (Sarbassov et al, 2006), and, moreover, it has been recently reported that mTORC2, but not mTORC1, is required for mGluR-LTD (Zhu et al, 2018). In line with these results, it is well established that inhibiting actin polymerization/depolymerization blocks mGluR-LTD (Zhou et al, 2011) and that dendritic spines elongate in response to mGluR activation, correlating with AMPA receptor (AMPAR) endocytosis (Vanderklish and Edelman, 2002;Zhou et al, 2011).…”
Section: Introductionmentioning
confidence: 81%
“…The relative contribution of these cascades to the protein synthesis necessary for mGluR-LTD is nevertheless unclear (for a review see Bhakar et al 2012). Interestingly, it has been recently shown that mTORC2, but not mTORC1, is required for mGluR-LTD (Zhu et al, 2018). mTORC2 regulates actin cytoskeleton and, in fact, actin polymerization-depolymerization inhibition abolishes mGluR-LTD (Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tsc2 +/− mice have reduced hippocampal protein synthesis rates instead of the predicted excessive protein synthesis from mTOR hyperactivation [2]. In addition, a recent study challenged the role of mTORC1 in hippocampal mGluR-LTD, arguing that mTORC2 is the major regulator of this form of synaptic plasticity [18,19] but see [13,20]. MGluR1/5 signaling can also regulate translation factors to suppress global protein synthesis, such as phosphorylation of eukaryotic initiation factor 2 alpha and eukaryotic elongation factor 2 (eEF2), which are both necessary for mGluR-LTD [18,21].…”
Section: Introductionmentioning
confidence: 99%